Sm protein methylation is dispensable for snRNP assembly in Drosophila melanogaster. - Gonsalvez, G.B.; Praveen, K.; Hicks, A.J.; Tian, L.; Matera, A.G. (RNA (New York, N.Y.), 2008)
Sm proteins form stable ribonucleoprotein (RNP) complexes with small nuclear (sn)RNAs and are core components of the eukaryotic spliceosome. In vivo, the assembly of Sm proteins onto snRNAs requires the survival motor neurons (SMN) complex. Several reports have shown that SMN protein binds with high affinity to symmetric dimethylarginine (sDMA) residues present on the C-terminal tails of SmB, SmD1, and SmD3. This post-translational modification is thought to play a crucial role in snRNP assembly. In human cells, two distinct protein arginine methyltransferases (PRMT5 and PRMT7) are required for snRNP biogenesis. However, in Drosophila, loss of Dart5 (the fruit fly PRMT5 ortholog) has little effect on snRNP assembly, and homozygous mutants are completely viable. To resolve these apparent differences, we examined this topic in detail and found that Drosophila Sm proteins are also methylated by two methyltransferases, Dart5/PRMT5 and Dart7/PRMT7. Unlike dart5, we found that dart7 is an essential gene. However, the lethality associated with loss of Dart7 protein is apparently unrelated to defects in snRNP assembly. To conclusively test the requirement for sDMA modification of Sm proteins in Drosophila snRNP assembly, we constructed a fly strain that exclusively expresses an isoform of SmD1 that cannot be sDMA modified. Interestingly, these flies were viable, and snRNP assays revealed no defects in comparison to wild type. In contrast, dart5 mutants displayed a strong synthetic lethal phenotype in the presence of a hypomorphic Smn mutation. We therefore conclude that dart5 is required for viability when SMN is limiting.